Ordinance No. 30: Concealed Weapons, in RED LODGE PICKET, Sep. 12, 1893, at 3, § 1 - (:unkn) unknown (My University, 1893)
It shall be unlawful after the passage of this ordinance for any person, within the limits of this town, to carry concealed on his person or under his clothes any pistol or revolver, or any other dangerous or deadly weapon, except by permission from the Mayor in writing, which permit shall state the period of time for which it is granted
Keywords: CARRY - CONCEALED